Density Functional Theory Studies on the Synthesis of Poly(α-Amino Acid)s Via the Amine-Mediated Ring Opening Polymerizations of N-Carboxyanhydrides and N-Thiocarboxyanhydrides - Bai, Tianwen; Zheng, Botuo; Ling, Jun (Frontiers in Chemistry, 2021)
To synthesize well-defined poly(-amino acid)s (PAAs), ring opening polymerizations (ROP) of cyclic monomers of -amino acid N-carboxyanhydrides (NCAs) and N-thiocarboxyanhydrides (NTAs) are most widely used. In this mini-review, we summarize the mechanism details of the monomer preparation and ROP. Density functional theory (DFT) calculations provide evidences to reveal the mechanisms together with experimental phenomena in the past decades. The detailed discussion includes normal amine mechanism (NAM) and the selectivity of the initiators bearing various nucleophilic groups.